Cast-in-place, ambiently-dried, silica-based, high-temperature insulation. (1st April 2017) - Cheng, Eric Jianfeng; Sakamoto, Jeff; Salvador, James; Wang, Hsin; Maloney, Ryan; Thompson, Travis
Abstract: A novel sol-gel chemistry approach was developed to enable the simple integration of a cast-in-place, ambiently-dried insulation into high temperature applications. The insulation was silica-based and synthesized using methyltrimethoxysilane (MTMS) as the precursor. MTMS created a unique silica microstructure that was mechanically robust, macroporous, and superhydrophobic. To allow for casting into and around small, orthogonal features, zirconia fibers were added to increase stiffness and minimize contraction that could otherwise cause cracking during drying. Nano-sized titania powder was incorporated as an opacifier to reduce radiative heat transport. To assess relevance to high temperature thermoelectric generator technology, a comprehensive set of materials characterization experiments were conducted. The silica gel was thermally stable, retained superhydrophobicity with a water contact angle >150°, and showed a high electrical resistance >1 GΩ, regardless of heating temperature (up to 600 °C in Ar for 4 h). In addition, The silica-based thermal insulation exhibited a Young's modulus ∼3.7 MPa and a low thermal conductivity <0.08 W/(m.K) at room temperature before and after heat treatment (up to 600 °C in Ar for 4 h). Thus, based on the simplicity of the manufacturing process and the optimized material properties, we believe this technology can act as an effective cast-in-place thermal insulation (CTI) for thermoelectric generators and myriad other applications requiring improved thermal efficiency. Graphical abstract: A cast-in-place, ambiently-dried, silica-based thermal insulation was synthesized using methyltrimethoxysilane (MTMS) as the precursor. To allow for casting into and around small, orthogonal features, zirconia fibers were added to increase stiffness and minimize contraction that could otherwise cause cracking during drying. Nano-sized titania powder was incorporated as an opacifier to reduce radiative heat transport. The insulation showed a pearl necklace-like microstructure that was mechanically robust with a Young's modulus ∼3.7 MPa. Macroporous pores ranging from 3 to 30 μm penetrated the silica gel network. The gel retained its superhydrophobicity, high electrical resistance (>1 G Ω) and low thermal conductivity (∼0.08 W/(m.K)) after heating at 600 °C in Ar for 4 h. We believe this technology can act as an effective cast-in-place thermal insulation (CTI) for thermoelectric generator applications. Image